2006
DOI: 10.4049/jimmunol.176.3.1600
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus G Protein and G Protein CX3C Motif Adversely Affect CX3CR1+ T Cell Responses

Abstract: Interactions between fractalkine (CX3CL1) and its receptor, CX3CR1, mediate leukocyte adhesion, activation, and trafficking. The respiratory syncytial virus (RSV) G protein has a CX3C chemokine motif that can bind CX3CR1 and modify CXCL1-mediated responses. In this study, we show that expression of the RSV G protein or the G protein CX3C motif during infection is associated with reduced CX3CR1+ T cell trafficking to the lung, reduced frequencies of RSV-specific, MHC class I-restricted IFN-γ-expressing cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 50 publications
4
133
0
3
Order By: Relevance
“…interaction with the fractalkine receptor, CX3CR1, a key mediator of cell trafficking to the infected lung (15,21). Consistent with these findings, human polymorphisms showing reduced activity of either TLR4 (27) or CX3CR1 (28) were significantly overrepresented in studies of infants with severe RSV disease.…”
supporting
confidence: 73%
“…interaction with the fractalkine receptor, CX3CR1, a key mediator of cell trafficking to the infected lung (15,21). Consistent with these findings, human polymorphisms showing reduced activity of either TLR4 (27) or CX3CR1 (28) were significantly overrepresented in studies of infants with severe RSV disease.…”
supporting
confidence: 73%
“…However, the conserved cysteine-rich region of the G protein has homology with the fourth domain of the TNF receptor [80] and may inhibit components of the innate response by binding to TNFα or an unknown TNF homologue. Studies with rHRSV lacking the cysteine-rich region of the G protein suggest that although this region is not required for efficient viral replication in mice [139], it may play a role in suppressing the anti-viral T-cell response [56]. As mentioned previously, field isolates of BRSV have been identified that lack one or more of the cysteines in the central conserved region (see Sect.…”
Section: The Role Of the G Protein In The Pathogenesis Of Brsvmentioning
confidence: 99%
“…Moreover, the secreted form of the G protein has a chemokine-like motif (CX3C) that competes with fractalkine (CX3CL1) in binding to its receptor CX3CR1, thus reducing the CX3CR1 C T cells response. 116 HRSV Fusion (F) protein: this viral protein is required for the fusion of viral particle with the host cells 4 and also play a direct role in the ability of hRSV to decrease the proliferation of these cells by contact. 117 In fact, when Vero cells express the F protein or are infected with a version of hRSV that only have F protein on its surface, they reduce the proliferation and response to mitogen stimulus.…”
Section: Role Of Hrsv Proteins In Immunomodulationmentioning
confidence: 99%